To cut out to recall: image, translation and imagination of the Casa dos Braga - Nascimento, Josyane Malta (Laboratório Editorial FCL-UNESP, 2008)
This work proposes to investigate the relation between writing about oneself, that is, the narrative of personal memories and photography. We will consider that memories can be processed as an act of photographing personal experiences. In the theoretical corpus selected the studies of Roland Barthes in the books A câmara clara and O óbvio e o obtuso: ensaios críticos III, in which the author works with considerations about the photographic image, will be of great importance. Also the theoretical question of Walter Benjamin about translation may emerge, when we think of memory as a possibility of translation of personal experiences. The memory book Casa dos Braga, by the Brazilian writer Rubem Braga, will be used as a literary corpus, so that we can articulate the theoretical questions proposed.